Adaptive chattering-free terminal sliding mode control for a coordinate measuring machine system. (December 2021) - Tang, Rongchuan; Shao, Ke; Xu, Feng; Wang, Xueqian; Liang, Bin
Abstract: In this paper, an adaptive chattering-free terminal sliding mode (ACTSM) controller is proposed for the high-precision control of a coordinate measuring machine (CMM) system based on nonsingular terminal sliding mode. Different from the conventional chattering-free full-order sliding mode (FOSM) controller, a nested adaptive law is introduced in this paper to remove the requirements for upper bounds of disturbances and their derivatives. As a result, overestimation and underestimation are both fully eliminated. Lyapunov analysis verifies that under the proposed ACTSM controller, the tracking error of motor speed will converge to zero in finite time. Experiments on a real coordinate measuring machine are conducted to demonstrate the advantages of the proposed method with smaller speed tracking errors and subsequently smaller measurement errors compared to conventional proportional–integral (PI) control and FOSM control. Graphical abstract: Highlights: Nonsingular TSM control is implemented in a CMM system for the first time. An ACTSM controller is proposed to remove the requirements for upper bounds of disturbances and their derivatives. Experiments on a real CMM are conducted with smaller speed tracking errors and measurement errors.